Low Vitamin D Levels Predict Stroke in Patients Referred to Coronary Angiography - Pilz, Stefan; Dobnig, Harald; Fischer, Joachim E.; Wellnitz, Britta; Seelhorst, Ursula; Boehm, Bernhard O.; März, Winfried (Stroke (1970), 2008)
Background and Purpose— Vitamin D deficiency is common among the elderly and may contribute to cerebrovascular diseases. We aimed to elucidate whether low vitamin D levels are predictive for fatal stroke. Methods— The LUdwigshafen RIsk and Cardiovascular Health (LURIC) study includes 3316 patients who were referred to coronary angiography at baseline between 1997 and 2000. 25-Hydroxyvitamin D [25(OH)D] and 1,25-dihydroxyvitamin D [1,25(OH)2D] were measured in 3299 and 3315 study participants, respectively. To account for the seasonal variation of vitamin D metabolites, we calculated z values for the 25(OH)D and 1,25(OH)2D concentrations within each month of blood draw. Results— During a median follow-up time of 7.75 years, 769 patients died, including 42 fatal (ischemic and hemorrhagic) strokes. When compared with survivors in binary logistic-regression analyses, the odds ratios (with 95% CIs) for fatal stroke were 0.58 (0.43 to 0.78; P <0.001) per z value of 25(OH)D and 0.62 (0.47 to 0.81; P <0.001) per z value of 1,25(OH)2D. After adjustment for several possible confounders, these odds ratios remained significant for 25(OH)D at 0.67 (0.46 to 0.97; P =0.032) and for 1,25(OH)2D at 0.72 (0.52 to 0.99; P =0.047). Z values of 25(OH)D and 1,25(OH)2D were also reduced in the 274 patients who had a history of previous cerebrovascular disease events at baseline. Conclusions— Low levels of 25(OH)D and 1,25(OH)2D are independently predictive for fatal strokes, suggesting that vitamin D supplementation is a promising approach in the prevention of strokes.